3D Printing: High‐Speed 3D Printing of Millimeter‐Size Customized Aspheric Imaging Lenses with Sub 7 nm Surface Roughness (Adv. Mater. 18/2018). Issue 18 (2nd May 2018) - Chen, Xiangfan; Liu, Wenzhong; Dong, Biqin; Lee, Jongwoo; Ware, Henry Oliver T.; Zhang, Hao F.; Sun, Cheng
Abstract : In article number1705683, Cheng Sun and co‐workers report a high‐speed 3D‐printing customized imaging lens of millimeter‐size. A significant increase in the fabricating speed is realized without compromising the dimensional accuracy and surface finish by employing highly parallel projection micro‐stereolithography and synergetic effects from grayscale photo‐polymerization and a meniscus equilibrium post‐curing process. This study opens new possibilities for rapid prototyping of freeform optics.